2023
DOI: 10.1038/s41598-023-30388-3
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis children with obesity are more vulnerable to air pollution: a cross sectional study

Abstract: The association between air pollution, allergic rhinitis (AR), and obesity has not been studied. From 2007 to 2011, 52 obese and 152 non-obese children (7–17 years old) with AR were recruited. Pediatric-Rhinoconjunctivitis-Quality-of-Life Questionnaire (PRQLQ) and nasal peak expiratory flow (NPEF) were tested. Association between the scores and rates of the two tests and mean air pollutant concentrations within 7 days before the tests were compared. When exposed to higher concentrations of CO, PM10, and PM2.5,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…A nationwide study in the United States found that central obesity in children was associated with reduced odds of AR, regardless of gender [33]. Additionally, a study in Korea found that obesity in children with AR was associated with increased vulnerability to air pollution, leading to exacerbated AR symptoms [45]. The precise mechanisms linking obesity to worsened allergies and AR symptoms remain unclear.…”
Section: Obesity Allergic Rhinitis and Osasmentioning
confidence: 99%
“…A nationwide study in the United States found that central obesity in children was associated with reduced odds of AR, regardless of gender [33]. Additionally, a study in Korea found that obesity in children with AR was associated with increased vulnerability to air pollution, leading to exacerbated AR symptoms [45]. The precise mechanisms linking obesity to worsened allergies and AR symptoms remain unclear.…”
Section: Obesity Allergic Rhinitis and Osasmentioning
confidence: 99%
“…Obesity-induced increases in leptin levels may contribute to heightened inflammation and more severe symptoms through its interaction with interleukin-1 β (IL-1β) [56]. Obesity negatively influences the severity of AR when children with AR experience higher carbon monoxide (CO) and ambient particles ≤ 10 µm in diameter (PM 10 ) but not in non-obese children with AR [57]. Thus, obesity among children with AR was linked to heightened susceptibility to air pollution, resulting in worsened AR symptoms [57].…”
Section: Diet-induced Obesity Allergic Rhinitis and Obstructive Sleep...mentioning
confidence: 99%
“…Obesity negatively influences the severity of AR when children with AR experience higher carbon monoxide (CO) and ambient particles ≤ 10 µm in diameter (PM 10 ) but not in non-obese children with AR [57]. Thus, obesity among children with AR was linked to heightened susceptibility to air pollution, resulting in worsened AR symptoms [57]. The specific mechanisms that connect obesity to the deterioration of allergies and AR symptoms remain uncertain.…”
Section: Diet-induced Obesity Allergic Rhinitis and Obstructive Sleep...mentioning
confidence: 99%
“…Obesity, considered a disease to some extent [4], is somehow characterized by the accumulation of excess body fat that may have adverse effects on health. Several studies have demonstrated obesity as a chronic in ammatory condition related to persistent systemic in ammation of the respiratory tract, such as asthma [5,6] and allergic rhinitis [7]. However, the effect of obesity in sinusitis remains controversial [8][9][10].…”
Section: Introductionmentioning
confidence: 99%